Pre-Treatment With hCG Before Ovsynch (-3hCG/Ovsynch) May be an Alternative to the Progestagen-Based Ovsynch Protocol in Cows With Ovarian Follicular Cyst - Dogan, Halef; Bayraktar, Metin; Kutlu, Metehan; Yenilmez, Kudret; Dogan, Hasan (Wiley, 2025)
Cystic ovarian disease is one of the leading causes of infertility in dairy cows. In this experimental field study, the comparative efficacy of the -3hCG/Ovsynch protocol (pre-treatment with hCG before Ovsynch) was investigated alongside the Ovsynch and the progestagen-based Ovsynch protocol. A total of 45 dairy cows with follicular cyst (FC) were enrolled in the study. The cows were randomly divided into three equal groups: in the first group, the Ovsynch-48 protocol (Day 0 GnRH, Day 7 PGF(2 alpha), Day 9 GnRH and fixed-time artificial insemination (FTAI) 16-20 h later); in the second group, the CIDR-synch protocol (Day 0 GnRH and the insertion of CIDR into the vagina for 7 days, Day 7 PGF(2 alpha), Day 9 GnRH and FTAI 16-20 h later); and in the third group, the -3hCG/Ovsynch protocol (3000 IU hCG pre-treatment before initiation of the Ovsynch-48 protocol) were applied. Blood samples were collected on Day -3, 0, 3 and 7, and serum progesterone levels were measured. Transrectal sonography of the ovaries was performed on Day -3, 0, 3 and 7 for ovarian dynamics (follicular development, presence of FC, measurement of diameter and wall thickness of FC) throughout the protocols. Cows were fixed-time artificially inseminated. On Day 13 (3 days after FTAI) and Day 45 (pregnancy diagnosis), ovarian ultrasonography was also performed to evaluate the cystic persistence (PC). hCG pre-treatment was found to be ineffective on follicular development in the early period of the -3hCG/Ovsynch protocol, but it significantly increased the diameter of the dominant follicle on Day 3 when compared to the Ovsynch and CIDR-synch protocols. The lifespan of the corpus luteum in the -3hCG/Ovsynch group was longer (> 4 days) than in the other protocols (< 4 days). Following the Ovsynch, CIDR-synch and -3hCG/Ovsynch protocols, the PC rates were found to be 54.5% (6/11), 45.4% (5/11) and 27.2% (3/11) on Day 13, and 27.2% (3/11), 27.2% (3/11) and 9.1% (1/11) on Day 45, respectively. Conception rates were found in Ovsynch (6/15), CIDR-synch (8/14) and -3hCG/Ovsynch (8/15) protocols as 40%, 57.1% and 53.3%, respectively. According to the findings, it was concluded that the -3hCG/Ovsynch protocol may be more effective than the Ovsynch protocol in the treatment of cows with FCs, can be used as an alternative to the CIDR-synch protocol and can be preferred especially in cows with uterine infection detected early in the postpartum period and in cases where the use of exogenous progesterone is contraindicated.
Keywords: cow; follicular cyst; hCG; Ovsynch; progesterone